Ethics in Law Enforcement: Analyzing the Police Professional Code of Ethics - Azzahrah, Shabrina; Tambun, Abigail Citra Tama; Balqis, Adinda Rahma; Prasna, Adeb Davega (Journal of Legal and Cultural Analytics, 2024)
The aims of this research are to examine the regulation of the police code of ethics, to comprehend the role of the police code of ethics in law enforcement, and to investigate the method for enforcing the code of ethics and the punishments that can be imposed on officers who dissolve the code of ethics. The normative legal research method was applied. This study employs a statue and a conceptual method. The legal materials used in this study come from both primary and secondary legal sources. The analysis found that every police officer must conduct themselves with dignity. The National Police Code of Ethics Commission, as well as other institutions such as the National Police Legal Function Bearer, National Police Commission of the Republic of Indonesia, Profession and Security of the National Police of the Republic of Indonesia, and National Police Public Relations Division, carry out the mechanism of The Code of Ethics Sanction in Law Enforcement. Furthermore, police officers who are found to have breached the code of ethics can face both ethical and administrative consequences.